Rail passenger crowding, stress, health and safety in Britain - Cox, Tom; Houdmont, Jonathan; Griffiths, Amanda (Elsevier Ltd, 2006)
There has long been a question as to whether crowding in rail passenger transport poses a threat to passenger health related to the experience of stress. A review of the scientific literature was conducted. Little rail-specific empirical research was identified. The more general research that does exist suggests that high-density environments are not necessarily perceived as crowded and that stress-related physiological, psychological and behavioural reactions do not necessarily follow from exposure to such environments. Several factors are identified that may moderate the impact of a high-density environment on perceptions of crowding and the subsequent experience and effects of stress. These include, inter alia, perceptions of control and predictability of events. However, if caused, the experience and effects of stress may be made worse by inadequate coach design that gives rise to discomfort. The model that emerges from these findings offers a suitable framework for the development of research questions that should help translate emerging knowledge into practical interventions, for the reduction of any adverse health outcomes associated with crowding.